2006
DOI: 10.1007/s10067-006-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic syndrome in one patient with adult-onset Still’s disease

Abstract: Macrophage activation syndrome (MAS) is an important complication seen in systemic for juvenile rheumatoid arthritis; until now, it has been reported in only a few cases of adult-onset Still's disease (AOSD). Here, we shall present a 50-year-old female patient who was using steroids and antimalarial drugs for AOSD, and who developed MAS during follow-up. The patient presented with febrile neutropenia, and the neutropenic period lasted for 15 days. The examination of bone marrow aspiration smears demonstrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…There are many reports of patients developing disseminated histoplasmosis while receiving TNF inhibitors (3,4). Patients with AOSD can develop MAS (8,9). However, this is a prime example of MAS caused by disseminated histoplasmosis in a patient with AOSD taking adalimumab.…”
mentioning
confidence: 98%
“…There are many reports of patients developing disseminated histoplasmosis while receiving TNF inhibitors (3,4). Patients with AOSD can develop MAS (8,9). However, this is a prime example of MAS caused by disseminated histoplasmosis in a patient with AOSD taking adalimumab.…”
mentioning
confidence: 98%
“…В то же время доказано, что ингибиторы ФНОα не эффективны и даже вредны в лечении РГЛ. Так, описаны несколько случаев РГЛ, связанного с применением этанерцепта [99,100]. Появились сообщения об эффективности тоцилизумаба при РЛГ, осложнившем БСРВ [101].…”
Section: таблицаunclassified
“… 83 , 87 More recently, several authors have reported on the successful management of RHL complicating adult or pediatric Still’s disease using IL-1 antagonists. 88 91 It is possible that higher doses of anakinra are required to treat Still’s disease-associated RHL (ie, 100 mg/6 hours). 91 On the contrary, anti-TNF-α has proven ineffective or even harmful in treating RHL.…”
Section: Life-threatening Complications Of Aosdmentioning
confidence: 99%